2015
DOI: 10.1186/s12935-015-0236-7
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-30b inhibits cell invasion and migration through targeting collagen triple helix repeat containing 1 in non-small cell lung cancer

Abstract: BackgroundNon-small cell lung cancer (NSCLC) is the largest histological subgroup of lung cancer and has increased in prevalence in China over the past 5 years. The 5-year survival rate has remained at 15–20 %, with a median survival of 8–12 months. The tumorigenesis and progression of NSCLC is orchestrated by numerous oncogene and anti-oncogene mutations and insights into microRNA function have increased our understanding of the process. Here, we investigated the effects of miR-30b on NSCLC cell invasion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Two independent analyses using lung cancer specimens revealed that overexpression of CTHRC1 strikingly associated with differentiation degree, clinical stage, T classification, lymph node metastasis, distant metastasis and cigarette smoke as well as with poor clinical survival time of the patients compared with patient with low CTHRC1 expression 11, 21. Furthermore, the observed results displayed that there were no significant differences between CTHRC1 and mRNA levels with different genders, ages or pathological types 22. Particularly, an ongoing study revealed that CTHRC1 interacted with microRNA-30b to decrease the ability of invasion and migration in NSCLC patients 22.…”
Section: Expression Profile In Several Representative Malignant Tumentioning
confidence: 91%
See 2 more Smart Citations
“…Two independent analyses using lung cancer specimens revealed that overexpression of CTHRC1 strikingly associated with differentiation degree, clinical stage, T classification, lymph node metastasis, distant metastasis and cigarette smoke as well as with poor clinical survival time of the patients compared with patient with low CTHRC1 expression 11, 21. Furthermore, the observed results displayed that there were no significant differences between CTHRC1 and mRNA levels with different genders, ages or pathological types 22. Particularly, an ongoing study revealed that CTHRC1 interacted with microRNA-30b to decrease the ability of invasion and migration in NSCLC patients 22.…”
Section: Expression Profile In Several Representative Malignant Tumentioning
confidence: 91%
“…Furthermore, the observed results displayed that there were no significant differences between CTHRC1 and mRNA levels with different genders, ages or pathological types 22. Particularly, an ongoing study revealed that CTHRC1 interacted with microRNA-30b to decrease the ability of invasion and migration in NSCLC patients 22. These results suggest that CTHRC1 overexpression is a valuable prognosis biomarker for NSCLC.…”
Section: Expression Profile In Several Representative Malignant Tumentioning
confidence: 91%
See 1 more Smart Citation
“…in vitro examinations revealed that mir-30b inhibits cell invasion and migration through targeting and downregulating cthrc1 of a549 and calu-3 cells. Not only was the expression of cthrc1 decreased, mmp-2 and mmp-9 expression was also reduced while Timp-1 expression was increased in mir-30b mimic transfected a549 and calu-3 cells 138 . Timp1 regulates extracellular matrix catabolism but the major effect in tumour tissue is promotion of cell growth and anti-apoptotic activity 139 .…”
Section: Mirnas Involved In Lymph Node Metastasismentioning
confidence: 96%
“…chen et al evaluated the expression of mir-30b in Nsclc (ref. 138 ). The median ± sd expression levels of mir-30b were associated with lymph node metastasis as follows: Nsclc patients lNm+ had 0.2147 ± 0.0670 levels; Nsclc patients lNm-had 0.3129 ± 0.1234 levels.…”
Section: Mirnas Involved In Lymph Node Metastasismentioning
confidence: 99%